Workers on the Streets, Representatives in Parliament: The Indonesian Trade Union Confederation (KSPI) Rejects the 2020 Job Creation Law - Zhafira Aura Pradipta; Kalista Berliana Putri; Muradi Muradi (Utan Kayu Publishing, 2025)
This study examines the role of the Indonesian Trade Union Confederation (KSPI) in rejecting the 2020 Job Creation Law using Hannah Pitkin's political representation theory framework. The enactment of the Job Creation Law, which was drafted behind closed doors, with minimal public participation, and laden with capital interests, confirms the existence of a crisis of substantive representation in the legislature. It is in this context that KSPI emerged as a non-legislative actor attempting to fill the representation vacuum through litigation, mass actions, media campaigns, and international solidarity networks. This study uses a literature review method, examining academic documents, labor union reports, media coverage, and Constitutional Court decisions. The analysis reveals a paradox: while the KSPI has succeeded in pushing labor issues onto the public agenda and winning a conditional unconstitutional ruling, substantive achievements remain limited because core policies remain intact. These findings confirm that substantive representation does not always have to originate from legislative institutions, but can also be articulated by labor unions or other civil society actors. However, the effectiveness of such representation depends heavily on the extent to which they are able to penetrate formal political structures and build broader coalitions outside the arena of street protests.